Nutritional and immunological effects of nano-particles in commercial poultry birds. Issue 2 (1st June 2019) - Anwar, M.I.; Awais, M.M.; Akhtar, M.; Navid, M.T.; Muhammad, F.
Abstract : The poultry industry is mainly scared by affected by infections due to microorganisms which reduce the growth rate and cause economic losses. Currently, vaccines and antibiotics are utilised to combat these infectious microorganisms, but irresponsible use of antibiotics may pose health risks to consumers, and there is a need for drug-free alternatives. Nanotechnology could reduce such risks and can improve the wholesomeness of poultry meat. This review discusses the current status of nanotechnology as it relates to improving poultry health by using various nano-particles (NPs). Silver-NPs at a dose rate of 900 ppm have been used in poultry to improve their growth performance in terms of body weight, feed intake and feed conversion ratio. NPs are thought to boost immunity in birds against numerous diseases. Gold-NPs improved the growth performance of poultry birds as well as detecting avian influenza virus with a detection limit of 2.2 pg/ml. Similarly, Copper-loaded chitosan-NPs supplementation at dose rate of 100 mg/kg feed improved growth performance, immunity, protein synthesis and caecal microbiota in broilers. Zinc oxide-NPs improved growth performance and showed anti-oxidative properties in broilers at the dose rate of 20 mg/kg. While, montmorillonite nano-composites at a level of 3 g/kg feed decreased the toxicity of aflatoxins in poultry birds. In conclusion, nanotechnology has the potential to reduce microbial load without resulting drug residues in poultry products, thus improving performance and immune status of poultry birds.